If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5d=3(d+6)
We move all terms to the left:
5d-(3(d+6))=0
We calculate terms in parentheses: -(3(d+6)), so:We get rid of parentheses
3(d+6)
We multiply parentheses
3d+18
Back to the equation:
-(3d+18)
5d-3d-18=0
We add all the numbers together, and all the variables
2d-18=0
We move all terms containing d to the left, all other terms to the right
2d=18
d=18/2
d=9
| 6n+3=16 | | 4(q-13)-12=-4 | | x2−9x−15=−5 | | (x*3)+5=20 | | x+2÷8=2 | | 167=60-x | | 2x-7=6(x+3) | | x-6-3x=-8-8x+5 | | 9y=10y-19 | | 11+5k=2+3k-3 | | 20-8u-8u=4(-5u-11) | | 12x^2=19x*10 | | 5•(x-7)-4=11 | | 4/9(x)=-8 | | 24+m+85=685 | | -18=10a+2 | | -16+11q=-14q+9(-19q+20) | | 4/9(x)=8 | | 7x=0.5(2x+4) | | 8x-45-10=15+6x | | 4b+12=84 | | B+9b+2=12 | | —16+z=20 | | /1x+11=15 | | 41/2x+7=12 | | 8/17=u/5 | | 7s-3s-4=20 | | 4.x=1/2 | | 1=12b | | -11-19b-16=-6+6(-5b-20) | | /x/1+11=15 | | 4.x=1/ |